Teaching mathematics: historical aspects (Research, Society and Development, 2020)
This article presents a historical discussion about mathematics, from its beginnings to teaching in the current context, and its relations with the teaching of discipline at school, highlighting the role of the teacher and teaching methods, conceiving this science beyond the classroom. Historically, this knowledge started to be developed from a need of society, since the Paleolithic period, before there was writing or civilizations as we know today: the counting process. Over the centuries, the rudimentary processes around calculations have been refined until the emergence and consolidation of the science known as mathematics. Therefore, it became an elementary discipline in schools, requiring, therefore, didactic-pedagogical skills for teaching, which has undergone significant changes. Because of this, it is essential that we are able to rediscover simpler and more dynamic ways of teaching it in the classroom, due to its importance for the daily practices of our students. This research presents a theoretical discussion, of a qualitative nature, guided methodologically in a bibliographic review with authors who discuss the history of the subject in question and its teaching. The results of this theoretical framework points to the need to re-signify the teaching and learning process, which requires investments, qualifications and training so that professionals, many of whom are still linked to basic teaching techniques, can oxygenate new possibilities of teaching, with practices of quality that aim at the real and satisfactory development of students beyond the school context.